Coprodutos do beneficiamento de girassol na dieta de ovinos confinados - Vargas, Luzia Elaine Domingues Pimenta (2017)
Ruminants, due to their peculiar digestive system, presents high capacity of consumption and digestion of a variety of byproducts generated by the agribusiness. In turn, sunflower processing for oil production generates byproducts that, due to the high volume, can cause organizational and environmental problems. Thus, the objective of this research was to evaluate the nutritional viability of the inclusion of byproducts from the sunflower processing to the sheep diet. In the Laboratory of Animal Metabolism in the University Campus of Rondonópolis-MT, two independent experiments were performed. For each experiment, 20 uncastrated lambs weighing approximately 30 kg body weight (CP) were housed in metabolism cages and arranged in a randomized complete block design with five replicates. The chemical composition of the ingredients, rations, leftovers, faeces and urine were evaluated, from which the intakes and digestibilities of the dry matter (DM) and nutrients and nitrogen balance (BN) were quantified. In both experiments the diets were isoprotein with a bulky: concentrate ratio (V: C) of 60: 40%, based on MS. Data were submitted to analysis of variance and regression using statistical software R. In the first experiment was evaluated the inclusion of 0; 12; 24; and 36% of sunflower residue (RG) to replace corn silage in the diet. The consumption of DM, organic matter (OM), crude protein (CP), acid detergent fiber (FDA), neutral detergent insoluble nitrogen (NIDN) and non-fibrous carbohydrates (CNF) were not influenced (P> 0.05) by the inclusion of GR. Mean values of 1271.70 and 158.8 g day-1, respectively, were recorded for MS and PB intakes. However, there was an influence (P <0.05) on the consumption of neutral detergent fiber (FDN) and ethereal extract (EE), registering a reduction of 3.39 g day-1 and an increase of 2.84 g day -1 for Each percentage unit of RG added in the diet, respectively. The digestibility coefficients (CD) of DM; PB and FDN were 71.11; 70.60; and 59.91%, respectively. There was an increasing linear effect for NDT with increases of 0.31% for every 1% inclusion of RG in the diet. There was no influence of byproduct on ingested nitrogen (NI), nitrogen excreted by feces (NF), nitrogen absorbed (NA) and nitrogen retained (NR), but nitrogen excretion via urine (NU) reached the maximum when supply was 13.74% RG. It was concluded that RG presents good potential for use in sheep feeding. In the second experiment, the inclusion of 0; 9.3; 18.6 and 27.9% of sunflower meal (FG) replacing 0, 33, 66 and 100% of the soybean meal (FS) in the concentrated ration, which corresponded to 0; 3.7; 7.4; 11.1% FG in the dietary MS, respectively. The results indicated absence of significant effect (P <0.05) for consumption and digestibility of DM, OM, PB, EE, FDN, FDA, and CNF. The mean values for DM, PB and FDN consumption were 2.9; 0.4 and 1.3% PC day-1, respectively and the digestibility was 69.6; 72.84; 53.60%, respectively. There was a linear increase (P <0.05) for the consumption of NIDN and NIDA, estimating increments of 0.19 and 0.04 g day-1 for each unit of GF added in the concentrate ration, respectively. The values of NI, NF, NU, NA and RN were not influenced by the inclusion of FG in the animals' diet. Mean values of 13.77 were recorded; 6.84; 6.04; 16.92; and 10.78 g day-1, respectively for NI, NF, NU, NA and RN. It is concluded that in diets for sheep with 40% of concentrate the FG can be used as exclusive source of protein in substitution to FS.